KAJIAN PERILAKU SANITASI MASYARAKAT SETELAH MPA-PHAST DI KELURAHAN TOTOLI KECAMATAN BANGGAE KABUPATEN MAJENE SULAWESI BARAT - , Sitti Nur Aliah, ST ([Yogyakarta] : Universitas Gadjah Mada, 2012)
MPA-PHAST (Methodology Participatory Assessment Participatory Hygiene and Sanitation Transformation) is a methodology to help the community, the program managers and decision makers to achieve service of sustainability and equity as well as to identify and to solve the problems of hygiene and sanitation. MPA-PHAST used byPAMSIMASas a tooltoacceleratepublic awarenessrelating to the healthy behaviorandsanitation. The purposes of this study namely: 1) To describe the public sanitation behavior before and after MPA-PHAST, 2) To identify the factors that influence the public sanitation behavior. This research used qualitative descriptive study which describes the facts about the changes of sanitation behavior of Totoliâs community after application MPA- PHAST. Determination of the sample used purposive sampling techniques, namely the community, the government and facilitator. Data analysis was performed by induction and categorization. Result of the research showed that before and after MPA-PHAST not changed significantly though the sanitation facilities increasing the water supply, latrines, waste water and garbage. Targetted zero open defecation was not reached. Factors that affected the acquired predisposing factor were: self-will community to provide the facility,, attitude toward sanitation facility, knowledge, ability of the community and understanding of sanitation facility model . Some of identified enabling factor were: Government policy, Coordination and Strategy. And reinforcing factors were:understanding program and the community involvement. These themes werederivedfromthe lack of ofmotivation, participationandinstitutional. That were accordingly, arrange asstrategyforsanitationbehavior.